Lichens survive in space: Results from the 2005 LICHENS experiment - Sancho, Leopoldo G.; de la Torre, Rosa; Horneck, Gerda; Ascaso, Carmen; de los Rios, Asunción; Pintado, Ana; Wierzchos, Jacek; Schuster, Martin (Astrobiology, 2007)
This experiment was aimed at establishing, for the first time, the survival capability of lichens exposed to space conditions. In particular, the damaging effect of various wavelengths of extraterrestrial solar UV radiation was studied. The lichens used were the bipolar species Rhizocarpon geographicum and Xanthoria elegans, which were collected above 2000 m in the mountains of central Spain and as endolithic communities inhabiting granites in the Antarctic Dry Valleys. Lichens were exposed to space in the BIOPAN-5 facility of the European Space Agency; BIOPAN-5 is located on the outer shell of the Earth-orbiting FOTON-M2 Russian satellite. The lichen samples were launched from Baikonur by a Soyuz rocket on May 31, 2005, and were returned to Earth after 16 days in space, at which time they were tested for survival. Chlorophyll fluorescence was used for the measurement of photosynthetic parameters. Scanning electron microscopy in back-scattered mode, low temperature scanning electron microscopy, and transmission electron microscopy were used to study the organization and composition of both symbionts. Confocal laser scanning microscopy, in combination with the use of specific fluorescent probes, allowed for the assessment of the physiological state of the cells. All exposed lichens, regardless of the optical filters used, showed nearly the same photosynthetic activity after the flight as measured before the flight. Likewise, the multimicroscopy approach revealed no detectable ultrastructural changes in most of the algal and fungal cells of the lichen thalli, though a greater proportion of cells in the flight samples had compromised membranes, as revealed by the LIVE/DEAD BacLight Bacterial Viability Kit. These findings indicate that most lichenized fungal and algal cells can survive in space after full exposure to massive UV and cosmic radiation, conditions proven to be lethal to bacteria and other microorganisms. The lichen upper cortex seems to provide adequate protection against solar radiation. Moreover, after extreme dehydration induced by high vacuum, the lichens proved to be able to recover, in full, their metabolic activity within 24 hours.
Keywords: lithopanspermia; eobiology; lichens; BIOPAN experiment